Evaluasi atau Penilaian Pembelajaran bagi Anak Berkebutuhan Khusus di SMK Muhammadiyah 1 Wates - Nurtanti, Sendi; Lifeaningrum, Lail Syageta; Husna, Difa Ul (STAI Denpasar Bali, 2023)
Learning evaluation is a process or activity to determine values, criteria, or behavior in learning. Children with special needs require special assistance & supervision. This type of research is empirical research, namely research with field data as the main data source. This type of research obtains data using field research, namely by observation, the researcher makes on-site observations of the research object to be observed using the five senses. Research Results In inclusive learning, the teacher prepares an individual assessment book which contains a summary of all student learning outcomes and each student receives the same attention but is given according to their needs. There are adjustments in techniques/methods/strategies in carrying out learning outcomes assessments. For example, students with visual impairments when assessing learning outcomes need to use riglets, pens, tape recorders, Braille typewriters and loops. If there is an oral test, then for students with hearing impairments there needs to be facial direction and the use of speech reading or lip reading, and when the teacher speaks it must be clear and the mouth movements are slow so that the student can understand, or even when specifically using sign language.